The Significant Impact from Syria’s White Helmets Organization Toward the Condition of Syria’s Civil Society: Under Bashar al-Assad Administration - Muhammad Fawwaz Syafiq Rizqullah (Insignia: Journal of International Relations, 2021)
The aim of this paper is to analyze the role of the white helmets organization by involving in the world peace mission in Syria. The condition of Syrian civil society is very horrifying after Bashar al-Assad become the leader of Syria a thousand of people are suffering because of his policy and also creating tension between Islamic Sunni and Syiah in Syria. However, White Helmets Organization is one of the Organization that concern on mitigate and help the society under conflict and one of their concern nowadays is how to help Syria society from trouble condition. By using alternative and transformative regionalism theory and also qualitative method this research found if the reason behind why White Helmets Organization take any action is purely because a sense of humanitarian and by involving in this mission White Helmets has given a thousand of beneficial that make Syrian society felt better in many aspect of life. This research also found a lot of obstacle that White Helmets Organization dealing with due to the conflict area.